Blueberry Supply Chain in Peru: Planning, Integration and Execution - Edgar Ramos P.; Karen A. Espichan; Kerly T. Rodriguez; Zilin Wu; Wei-Shuo Lo (International Journal of Supply Chain Management, 2018)
The Blueberry situation in Peru is in a stage of development, in which it is necessary to incorporate good management practices as well as productive to raise the competitiveness of the enterprises. The findings were synthesized and analyzed, to propose improvements and to support the growth of the small companies in the long term. The improvement case study is based on the best practices and supply chain models applied in the industry. Also, the research was based on sources of information from researchers with experience in evaluating and analyzing the supply chain of the perishable sector in different scenarios worldwide.